2021
DOI: 10.1007/s11469-021-00711-y
|View full text |Cite
|
Sign up to set email alerts
|

Problematic Social Network Use: Structure and Assessment

Abstract: Using social networks (SNs) inappropriately can lead to psychological problems. The objective of this study was to develop a new measuring instrument of problematic use of SNs. The sample comprised 1003 participants over 18 years old (M = 42.33; SD = 14.32). Exploratory factor analysis was performed with a randomly selected 30% of the sample, and confirmatory factor analysis with the remaining 70%. The reliability of the instrument was estimated, and evidence of validity in relation to the variables—anxiety, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 65 publications
1
8
0
1
Order By: Relevance
“… Problematic Use of SNs (PUS) Scale. The PUS is a self-report scale that examines the potential impact of social networking’s (SNs) use on addiction, with a focus on the way SNs are being used in a comparative manner, and evaluating problematic SN use without a specific focus on a particular social media network, and therefore can be generalized to various SNs [ 34 ]. The instrument is composed of 18 Likert-type items with five possible options (1 = completely disagree, 5 = completely agree).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“… Problematic Use of SNs (PUS) Scale. The PUS is a self-report scale that examines the potential impact of social networking’s (SNs) use on addiction, with a focus on the way SNs are being used in a comparative manner, and evaluating problematic SN use without a specific focus on a particular social media network, and therefore can be generalized to various SNs [ 34 ]. The instrument is composed of 18 Likert-type items with five possible options (1 = completely disagree, 5 = completely agree).…”
Section: Methodsmentioning
confidence: 99%
“…Beside addictive consequences, a key factor in PUSN, known as negative social comparison [ 33 ], is studied as the second component of the PUSN scale [ 34 ]. Social comparison is defined as a self-evaluation where the person compares themselves to others [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…En primer lugar, los resultados obtenidos sugieren que la educación en el uso seguro y responsable de las redes sociales es una necesidad clara que debe tener lugar antes de la edad en la que legalmente se pueden usar. Un uso inadecuado de la red puede exponer a los menores a posibles peligros (Astorga-Aguilar y Schmidt-Fonseca, 2019;González-Nuevo et al, 2021;Martinez-Libano, et at., 2022;Tejada, et al, 2019). Según el informe de EU Kids Online (Garmendia et al, 2019) algunos riesgos son: el ciberbullying, el sexting, el grooming, la adicción a internet, la pornografía, exponer su vida privada y contactar con extraños.…”
Section: Discussionunclassified
“…Seventy-eight percent of participants in one study reported comparison was the most effective to maintain a high level of quality of life (Graham Beaumont & Kenealy, 2004). SCT identifies two forms of social comparison: upward and downward (González-Nuevo et al, 2021). Upward comparison may occur when working with a PS worker who has recovered from a similar challenge, which may result in the service user feeling more hopeful that they too can overcome the challenge.…”
Section: How Peer Support Workmentioning
confidence: 99%